SINERGITAS JOB SAFETY ANALYSIS DAN MANAJEMEN PELAYANAN PUBLIK SEBAGAI KATALISATOR KESELAMATAN KERJA DI PELABUHAN INDONESIA - Dewi, Shinta Mardiana; Kartikasari, Ririn Dwi Astuti; Pramudya, Akbar (JURNAL ILMIAH EDUNOMIKA, 2024)
The port sector in Indonesia has experienced significant development in supporting the national economy, but it also has a high risk of work accidents, particularly related to unsafe actions and unsafe conditions that contribute to the increasing accident rate. This research explores risk mitigation through the Job Safety Analysis (JSA) approach and public service management theory, with the aim of identifying and managing safety risks in the port sector. Data shows a 25% increase in workplace accidents over the past five years, with 60% caused by unsafe actions and working conditions. This research emphasizes the importance of safety training, strict supervision, and equipment maintenance to create a safe working environment. It was found that the structured implementation of Job Safety Analysis can reduce accidents by up to 30%, although its application in Indonesia is still limited, especially in small companies. Moreover, the role of the government as a regulator and facilitator is crucial in enhancing compliance with safety standards. By integrating Job Safety Analysis and public service management, this research offers a comprehensive approach that is expected to enhance workplace safety and support the operational sustainability of the logistics sector. This research is expected to serve as a foundation for the formulation of more effective and sustainable occupational safety policies in the port sector.